1997
DOI: 10.1038/sj.onc.1201031
|View full text |Cite
|
Sign up to set email alerts
|

Yeast two-hybrid in vivo association of the Src kinase Lyn with the proto-oncogene product Cbl but not with the p85 subunit of PI 3-kinase

Abstract: Ligand binding of multi-chain antigen receptors and hematopoietin/cytokine receptors results in rapid activation of protein tyrosine kinase (PTK)-dependent signalling molecules such as phosphatidylinositol 3-kinase (PI 3-kinase). Co-precipitation studies have shown that Srcrelated PTK, such as Lyn, associates with the p85 regulatory subunit of PI 3-kinase via SH2 and SH3 domain binding with their cognate ligands. More recent studies have shown that the proto-oncogene product Cbl co-precipitates with p85 follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 12 publications
3
36
2
Order By: Relevance
“…Similar results were seen with LY294002, which reversibly inhibits PI 3-kinase by competing for its substrate binding site (data not shown). Through coordination of SH3 and SH2 domains with proline-rich and phosphotyrosine motifs, Lyn can couple to PI 3-kinase via an adaptor molecule, such as Cbl (Dombrosky-Ferlan and Corey, 1997;Hunter et al, 1999). We observed that G-CSF-induced tyrosine phosphorylation of Cbl also correlated strictly with G-CSF-induced proliferation (Figure 5c).…”
Section: G-csf Stimulation Of Pi 3-kinase and Cbl And The Contributiosupporting
confidence: 50%
“…Similar results were seen with LY294002, which reversibly inhibits PI 3-kinase by competing for its substrate binding site (data not shown). Through coordination of SH3 and SH2 domains with proline-rich and phosphotyrosine motifs, Lyn can couple to PI 3-kinase via an adaptor molecule, such as Cbl (Dombrosky-Ferlan and Corey, 1997;Hunter et al, 1999). We observed that G-CSF-induced tyrosine phosphorylation of Cbl also correlated strictly with G-CSF-induced proliferation (Figure 5c).…”
Section: G-csf Stimulation Of Pi 3-kinase and Cbl And The Contributiosupporting
confidence: 50%
“…PI3K is a downstream target of integrin-FAK/SFK pathways and can be activated through various and nonmutually exclusive pathways (34 -36). Upon integrin ligation, activation of PI3K can result from the binding of the Src homology 3 domain of Src with a proline-rich region within the p85 subunit of PI3K or through interactions between p85 with tyrosine-phosphorylated docking proteins such as Cb1 (22,23,37). Integrin-dependent FAK autophosphorylation on Tyr 397 may lead to the recruitment of Src homology 2 domain containing signaling proteins such as PI3K (22).…”
Section: Discussionmentioning
confidence: 99%
“…As these assays do not measure the relative strength of association, we cannot exclude contribution of sequences outside the SH3 domain to efficient binding. The 516-535 proline-rich cluster of human GADD34 and the homologous 511-530 cluster of MyD116 are structurally the most likely sites responsible for the interaction with the SH3 domain of Lyn because they conform the consensus Lyn SH3 binding site (26,27). Interestingly, a deletion overlapping the proline-rich cluster of GADD34 has been reported to abrogate binding of HRX leukemic fusion proteins (6), implicating this region of GADD34 as a site of multiple protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…pcDNA3-Lyn and its K275R mutant have been described (17). Glutathione S-transferase (GST)-Lyn bacterial expression constructs are derivatives of pGEX-2T (Amersham Pharmacia) carrying Lyn cDNA fragments (26). All DNA constructs were verified by sequencing.…”
Section: Methodsmentioning
confidence: 99%